IMPLEMENTATION E-GOVERNMENT IN DEVELOPMENT SERVICE E-KTP IN NGALIYAN CITY DISTRICT OFFICE SEMARANG - Mita Tiara (GEMA PUBLICA, 2023)
One of the government's efforts to improve the quality of public services namely with utilise progress technology information in process governance. This is known as e-government or administration of electronic or internet-based government. As is system e-government, expected every agency service public can provide an increase in the quality of public services that are more transparent, effective and efficient. Online services can be accessed by the District community Excavations, but there are still a number of obstacles in operation. Objective of this study to determine the application of e-government in making E- ID card on Service Subdistrict Dig. As for technique collection data that is interviews, documentation and observation. The research method used is qualitative with descriptive type with informant selection technique that is purposive sampling And For test validity data, researcher triangulation source. Results study show that service public in Subdistrict damn city Semarang still has obstacles in its implementation, namely related to servers and networks that sometimes have problems, besides the necessary socialization improved so that increasing awareness public And bureaucrat in utilise e-development government in City Semarang.Kata Kunci:E-Government, Service, E-KTP